Ectomycorrhizal Fungal Transformation of Dissolved Organic Matter: Consequences for Reductive Iron Oxide Dissolution and Fenton-Based Oxidation of Mineral-Associated Organic Matter - Krumina, Lelde; Op De Beeck, Michiel; Meklesh, Viktoriia; Tunlid, Anders; Persson, Per (Frontiers in Earth Science, 2022)
Recent studies have shown that dissolved organic matter (DOM) decomposed by ectomycorrhizal (ECM) fungi increases adsorptive properties of organic matter towards soil mineral surfaces. Concomitantly, ECM fungi secrete secondary metabolites with iron reducing capacity that are thought to participate in non-enzymatic Fenton-based decomposition of DOM. The aim of this study was to investigate if the iron reduction induced by the ECM fungus Paxillus involutus during organic matter decomposition was conserved in the decomposed DOM. We explored how the modified DOM reductively dissolved ferrihydrite and goethite nanoparticles and how these processes affected the reactions with H2O2 and the Fenton-based oxidation of mineral-associated organic matter. Culture filtrates were obtained from incubation of the ECM fungus on DOM from forest litter of a spruce forest. This modified DOM was separated by extraction into an ethyl acetate and a water fraction. These fractions were reacted with ferrihydrite and goethite in absence and presence of H2O2. Dissolved Fe2+ and HO• were measured and the reactions at the iron oxide-water interfaces were monitored in real-time with in-situ IR spectroscopy. Experiments showed that decomposition of DOM by P. involutus generated a modified DOM that displayed an increased and persistent reductive capacity. Most of the reductants were isolated in the aromatic- and carboxyl-dominated ethyl acetate fraction but some reduction capacity was also captured in the water fraction mainly containing carbohydrates. Reductive dissolution was more extensive for ferrihydrite than goethite, and this process generated significant oxidation of the DOM-ferrihydrite associations. Oxidation of adsorbed DOM was triggered by H2O2 via heterogenous and homogeneous Fenton reactions. These oxidation processes were favored by ferrihydrite because of a high reduction potential and a high efficiency of heterogeneous Fenton as compared to goethite. An optimal timing between the heterogeneous and homogeneous Fenton processes triggered extensive radical oxidation of the DOM-ferrihydrite associations generating a high concentration of surface-associated oxalate. Overall, the results show that organic matter associated with ferrihydrite may be more susceptible to radical oxidation than on goethite, and that fungal decomposition of DOM in general may have consequences for other important soil processes such as mineral dissolution, adsorption and initiation of radical reactions.